Computational modeling and data analysis in COVID-19 research - Rani Panigrahi, Chhabi; Pati, Bibudhendu; Rath, Mamata; Buyya, Rajkumar, 1970- (Boca Raton : CRC Press, Taylor & Francis Group, 2021)
"This book covers recent research on the COVID-19 pandemic. It includes the analysis, implementation, usage and proposed ideas and models with architecture to handle the COVID-19 outbreak. Using advanced technologies such as AI and ML techniques for data analysis, this book will be helpful to mitigate exposure and ensure public health"--
Machine learning implementations in COVID-19 / Kabita Kumari, S.K. Pahuja, and Sanjeev Kumar -- Analysis of COVID-19 data using consensus clustering technique / Arko Banerjee, Sunandana Mukherjee, Chhabi Rani Panigrahi, Bibudhendu Pati, and Rajib Mall -- MoBMGAN : modified GAN-based transfer learning for automatic detection of COVID-19 cases using chest X-ray images / Rajashree Nayak and Bunil Ku. Balabantaray -- Application and progress of drone technology in the COVID-19 pandemic : a comprehensive review / Vasundhara Saraf, Lipsita Senapati, and Tripti Swarnkar -- Smart war on COVID-19 and global pandemics : integrated AI and blockchain ecosystem / Anil D Pathak, Debasis Saran, Sibani Mishra, Madapathi Hitesh, Sivaiah Bathula, and Kisor K Sahu -- Machine learning based text mining in social media for COVID-19 / Tajinder Singh and Madhu Kumari -- Containing the spread of COVID-19 with IoT : a visual tracing approach / Pallav Kumar Deb , Sudip Misra, Anandarup Mukherjee, and Aritra Bandopadhyay -- Crowd-sourced centralized thermal imaging for isolation and quarantine / Sudershan Kumar, Prabuddha Sinha, and Sujata Pal -- Block chain technology for limiting the impact of pandemic : challenges and prospects / Suchismita Swain, Oyekola Peter, Ramasamy Adimuthu, and Kamalakanta Muduli -- A study on mathematical and computational models in the context of COVID-19 / Meera Joshi -- A detailed study on AI-based diagnosis of novel coronavirus from radiograph images / Malaya Kumar Nath and Aniruddha Kanhe -- Data analytics for COVID-19 / Shreyas Mishra.
OCLC-licensed vendor bibliographic record.
Keywords: COVID-19 (Disease) -- Research; MEDICAL / Public Health; MEDICAL / Biotechnology